A self-assembled, multicomponent water oxidation device. Issue 14 (18th January 2016) - Tóth, Rita; Walliser, Roché M.; Murray, Niamh S.; Bora, Debajeet K.; Braun, Artur; Fortunato, Guiseppino; Housecroft, Catherine E.; Constable, Edwin C.
Abstract : Langmuir–Blodgett (LB) and drop-cast (DC) films of [Ru(1 )3 ][PF6 ]2 /Co4 POM (1 = 4, 4′-bis( n nonyl)-2, 2′-bipyridine) on FTO function as water oxidation catalysts, and the catalyst evolves O2 for 600 min. Abstract : Langmuir–Blodgett (LB) and drop-cast (DC) films prepared from [Ru(1)3 ][PF6 ]2 and Co4 POM (1 = 4, 4′-bis( n nonyl)-2, 2′-bipyridine, Co4 POM = K10 [Co4 (H2 O)2 (α-PW9 O34 )2 ]) have been evaluated as water oxidation catalysts and their electrocatalytic performances are reported; DC films evolve more O2 per unit area than LB films and the catalyst is stable on an FTO surface for ≈500–600 minutes.